Cervical spine malformation in cornelia de lange syndrome: A report of three patients. Issue 6 (25th March 2014) - Bettini, Laura Rachele; Locatelli, Laura; Mariani, Milena; Cianci, Paola; Giussani, Carlo; Canonico, Francesco; Cereda, Anna; Russo, Silvia; Gervasini, Cristina; Biondi, Andrea; Selicorni, Angelo
<x xml:space="preserve">Abstract</x> Cornelia de Lange syndrome (CdLS) is a complex genetic disease with skeletal involvement mostly related to upper limb malformations. We report on three males with clinical and molecular diagnoses of CdLS. Besides typical CdLS features, all showed different cervical spine malformations. To the best of our knowledge, this is an unusual malformation in the CdLS phenotypic spectrum. © 2014 Wiley Periodicals, Inc.